Methodology for estimation of the annual electricity consumption of a typical bank with multiple branches - YURTSEVER, ÖZLEM; FIRAT, SENİYE ÜMİT (SPRINGER, 2021)
In the digital age, banks adopt energy-efficient, sustainable, and environmentally friendly methods. Such organizations with hundreds of branches and thousands of employees not only provide considerable energy efficiency opportunities but also offer significant possibilities with climate change-related investments. In order to manage, control, and mitigate electricity consumption, in-depth knowledge is required, since the banking operations heavily depend on electricity. It is a challenging but necessary step to calculate the electricity consumption of a sizeable banking organization consisting of different units, varying dimensions, and characteristics. The aim of this study is to develop a model for estimating the electricity consumption of the banks based on a few main research questions. A novel model is proposed to calculate the annual electricity consumption of banking organizations to contribute to the sustainability literature and best practice area on efficient use of natural resources. The model was developed using the field data from a major Turkish bank. In the model, nominal bank electricity consumption is proposed from a base month concept, representing the month with no heating and cooling. The breakdown of electricity consumption sources can easily be monitored for energy management by using the model. For the validation of the model, the total electricity consumption of five Turkish banks is calculated. The model results are in good agreement with the respective sustainability reports within 12% certainty. The validity and accuracy of the model are also tested for a Spanish bank that operates in ten countries and is one of the few bank conglomerates with an annual electricity consumption figure given in sustainability reports. The annual electricity consumption was estimated within 6.6% certainty. Thus, the annual electricity consumption of a bank can be estimated within an acceptable range using the number of branches, employees, and ATMs, supported by some reasonable assumptions.
Keywords: Energy management in banking sector; Electricity consumption model; Nominal bank electricity consumption; Sustainability; Carbon footprint